Intention to Use Digital Wallets Mediated by Attitude Toward Use with Perceived Usefulness, Perceived Ease of Use, and Perceived Security and Privacy as Predictors in Aceh Province - Della Fertiwi; Jasman J.; Sorayanti Utami (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to examine: 1) the effect of perceived usefulness, perceived ease of use, and perceived security and privacy on attitude toward using; 2) the effect of perceived usefulness, perceived ease of use, and perceived security and privacy on the intention to use digital wallets in Aceh Province; and 3) the mediating effect of attitude toward using in the relationship between perceived usefulness, perceived ease of use, and perceived security and privacy on the intention to use digital wallets in Aceh Province. The data collection method employed non-probability sampling with a total of 275 respondents. Data analysis was conducted using Partial Least Squares (PLS)-based Structural Equation Modeling (SEM) via SmartPLS 4.0. The findings show that perceived usefulness, perceived ease of use, and perceived security and privacy positively influence attitude toward using, which subsequently affects the behavioral intention to use. These results indicate that individuals in Aceh are more likely to adopt digital wallets when they perceive them as beneficial, user-friendly, and secure. Furthermore, the mediating role of attitude emphasizes its importance in strengthening the relationship between user perception and the intention to use digital wallet technology (t-value = 5.717, p-value = 0.000).